2023
DOI: 10.5483/bmbrep.2022-0146
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT-box transcription factor, NF-Y complex, mediates the specification of the IL1 neurons in C. elegans

Abstract: Neuronal differentiation is highly coordinated through a cascade of gene expression, mediated via interactions between transacting transcription factors and cis-regulatoryelements of their target genes. However, the mechanisms of transcriptional regulation that determine neuronal cell-fate are not fully understood. Here, we show that the nuclear transcription factor Y (NF-Y) subunit, NFYA-1, is necessary and sufficient to express the flp-3 neuropeptide gene in the IL1 neurons of C. elegans. flp-3 expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We chose to focus on nfya-1 because it showed the strongest phenotype. In C. elegans , loss of nfya-1 has previously been shown to affect vulva development, sensory neuron specification, and expression of specific cell fate transcription factors (Deng et al, 2007; Milton et al, 2013; Aklilu et al, 2022; Heo et al, 2022). NFYA-1/NFY-A is a subunit of the conserved, ubiquitously expressed trimeric repressor complex NF-Y/CBF.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to focus on nfya-1 because it showed the strongest phenotype. In C. elegans , loss of nfya-1 has previously been shown to affect vulva development, sensory neuron specification, and expression of specific cell fate transcription factors (Deng et al, 2007; Milton et al, 2013; Aklilu et al, 2022; Heo et al, 2022). NFYA-1/NFY-A is a subunit of the conserved, ubiquitously expressed trimeric repressor complex NF-Y/CBF.…”
Section: Resultsmentioning
confidence: 99%
“…We found that NFYA-1 loss caused gene expression to be abolished in certain neurons, such as the PVQs, as also shown recently for the IL1 neurons. (Heo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We found that NFYA-1 loss caused gene expression to be abolished in certain neurons, such as the PVQs, as also shown recently for the IL1 neurons. (Heo et al, 2022). However, the majority of neuronal genes analyzed showed ∼20-40% changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 min after transferring worms, fluorescence time lapse images were acquired using an Axio cam 208 color with 6.3X objective and ZEN software for 10 min duration. Images obtained at 0 min, 5min, and 10 min were analyzed using Image J 53 , and average fluorescence intensities were calculated by using GraphPad Prism.…”
Section: Methodsmentioning
confidence: 99%